PENERAPAN SISTEM PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PEMBERIAN KREDIT DI UNIT SIMPAN PINJAM SWAMITRA CABANG NUSUKAN - Lopita Rini, Dewi Saptantinah Puji Astuti & Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Banks are business entities that raise funds from the public in the form ofsavings and channel them to the public in the form of credit or other forms in orderto improve people's lives. In providing the credit necessary internal controls torealize an effective credit. The purpose of this study was to analyze the lendingprocedures and the effect of SPI on the provision of credit in USP Swamitra BranchNusukan. The data used in this study is qualitative data. The method of analysis inthis research is descriptive qualitative. Total population in this study were as manyas 13 people, then it deserves to be taken all to serve as a sample so this study is acensus study. The data used in this study are primary data obtained throughquestionnaires and observation. The results showed that the internal control and theprovision of credit has been very effective.Keywords: Internal Control Systems, Effektivitas Loans, Credit